Sustainability in Fashion Supply Chain Management - Soraya LIMA (Communications of International Proceedings, 2021)
Today, the sustainability challenge has become a relevant issue in the fashion industry. However, given that the request for sustainability is relatively new in this industry, research that could guide companies and organizations towards adopting this method is lacking. This study aims to understand the main practices and strategies used in fashion supply chain management. To accomplish these goals, a literature review was conducted, analyzing articles to compare different strategies and the consequences originated by applying them. The main conclusions obtained were examples of practices adopted to promote sustainability in supply chains, like eco-material production, green distribution and green retailing.
Keywords: Sustainability; Fashion; Strategies; Management.